2017
DOI: 10.1001/jamacardio.2016.5139
|View full text |Cite|
|
Sign up to set email alerts
|

Types of Myocardial Infarction Among Human Immunodeficiency Virus–Infected Individuals in the United States

Abstract: Importance The Universal Definition of Myocardial Infarction divides myocardial infarctions into different types. Type 1 myocardial infarctions result spontaneously from atherosclerotic plaque instability, whereas Type 2 myocardial infarctions occur in the setting of oxygen demand/supply mismatch such as with severe hypotension. Type 2 myocardial infarctions are uncommon in the general population but the frequency of Type 2 myocardial infarctions in HIV-infected individuals is unknown. Objective To character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 52 publications
1
71
2
Order By: Relevance
“…Distinguishing between types is important because T2MIs result from an imbalance of myocardial oxygen supply and demand caused by a diverse set of clinical conditions, including sepsis and cocaine-induced vasospasm 27 , whereas T1MIs are due to spontaneous atherosclerotic plaque rupture, erosion, or dissection with associated intraluminal thrombus 26 . We have shown 28 that T2MIs may account for a greater proportion of MIs among HIV-infected individuals as compared with what is seen in the general population due in part to the high prevalence of illicit drug use 29 and concurrent infections among HIV-infected individuals.…”
Section: Introductionmentioning
confidence: 83%
“…Distinguishing between types is important because T2MIs result from an imbalance of myocardial oxygen supply and demand caused by a diverse set of clinical conditions, including sepsis and cocaine-induced vasospasm 27 , whereas T1MIs are due to spontaneous atherosclerotic plaque rupture, erosion, or dissection with associated intraluminal thrombus 26 . We have shown 28 that T2MIs may account for a greater proportion of MIs among HIV-infected individuals as compared with what is seen in the general population due in part to the high prevalence of illicit drug use 29 and concurrent infections among HIV-infected individuals.…”
Section: Introductionmentioning
confidence: 83%
“…In a large study from the Centers for AIDS Research Network of Integrated Clinical Systems Cohort (CNICS), MI events were divided evenly between type 1 (atherosclerotic plaque instability/rupture) and type 2 (oxygen supply/demand mismatch), with type 2 MIs more common among patients <40 years, with lower CD4 counts, and with lower traditional CVD risk. 30 Earlier data demonstrated HIV-infected individuals with acute coronary syndromes (ACS) more likely to have single-vessel disease and high restenosis rates. 31 A recent study found HIV-infected individuals presenting with ACS to have a lower overall burden of coronary plaque compared with matched control patients, 32 but another found no difference in rates of severe coronary artery disease in HIV-infected versus matched control patients undergoing coronary angiography.…”
Section: The Impact Of Hiv On Ischemic Heart Diseasementioning
confidence: 99%
“…Including the assessment of subclinical atherosclerosis by measuring carotid artery intima-media thickness via ultrasound 11 or assessment of plaque features by coronary computed tomography angiography 12 will greatly improve risk stratification models. Further, in HIV+ patients with MI, it is important to diagnose specific types of MI as type 1 (caused by atherosclerosis) and type 2 (caused by bacteremia and recent use of recreational drugs) because they may require different treatment approaches 13 . Approximately half of myocardial infarction (MI) in HIV+ patients were type 2 MIs, which is higher than those in HIV negative patients 13 .…”
mentioning
confidence: 99%
“…Further, in HIV+ patients with MI, it is important to diagnose specific types of MI as type 1 (caused by atherosclerosis) and type 2 (caused by bacteremia and recent use of recreational drugs) because they may require different treatment approaches 13 . Approximately half of myocardial infarction (MI) in HIV+ patients were type 2 MIs, which is higher than those in HIV negative patients 13 . Taken together, general as well as specific management approaches will help better diagnosis, prevent and treat CVD in HIV+ patients.…”
mentioning
confidence: 99%